Prioritizing conservation and participatory mapping of ethnomedicinal plant resources in Western Ladakh, Indian trans-Himalaya - Angmo, Kunzes; Adhikari, Bhupendra S.; Rawat, Gopal S. (Frontiers in Forests and Global Change, 2025)
IntroductionThe Himalayan region is home to a rich array of wild medicinal plants that play a vital role in providing livelihoods and health security of the local communities. However, excessive exploitation of these plant resources driven by the growing demand from the market has resulted in rapid decline in several plant species. In this paper we provide the quantitative information on the population status and distribution pattern of the species frequently harvested from the wild in Western Ladakh, Indian Trans-Himalaya.MethodologyA Conservation Priority Score (CPS) was used to rank the species according to their density, frequency, usage diversity, and extractive pressure. We generated distribution maps of key species with the help of participatory rural appraisal (PRA) and field surveys. GIS was used to create a habitat suitability map. The survey areas were divided into four suitability classes based on aspects, degree of slope, and land use/cover. In order to guide conservation efforts, the distribution and usage patterns of medicinal plants were recorded, and the model’s accuracy was assessed using the Boyce index.ResultsOf the 84 species of medicinal plants 33 species fall under the category I (high priority) and 51 in category II. The majority of category I species were found in Wakha-chu (14 species), Suru (18 species) and the Lower Indus (19 species) valley. Valley High conservation priority species have very limited biomass available for harvesting as indicated by their low density and regeneration. Species in greater demand exhibit low density (0.01 to 12.6 individuals per m2). Highly traded species have been compared in terms of wide and narrow distribution range.ConclusionSeveral high priority species are facing the risk of local extinction in the study area. Therefore, there is an urgent need to initiate community led conservation action including closure of certain sites for extraction for a few years, fixing the limits of harvest and self-regulated rotational harvest for other areas. Local healers, ecologists and local communities need to come on same platform to evolve sustainable harvest plans and initiate long term monitoring following citizen science approach.